Supplier Selection for Small and Medium Enterprises: An Integrated DEMATEL- ANP Approach for Decision Making - Dutho Suh Utomo; Ridzky Zul Asdi; La Ode Ahmad Safar Tosungku (International Journal of Engineering, Science and Information Technology, 2026)
ABC Bakery, a small and medium enterprise (SME), relies heavily on high-quality raw materials to meet the growing demand of its local market. Given the importance of raw material quality in product outcomes, selecting the right supplier becomes a critical task. This research applies the DEMATEL and ANP methods to identify the most suitable supplier for ABC Bakery. Through DEMATEL, the relationships between various supplier selection criteria, including Price, Quality, Delivery, Flexibility, and Responsiveness, are analysed to understand how these factors interrelate. The ANP method is then used to perform pairwise comparisons of both the criteria and the suppliers. The results reveal that Price and Quality are the most influential factors in the supplier selection process, with Price having the greatest weight, followed by Quality. On the other hand, Delivery, Flexibility, and Responsiveness have relatively lower weights, indicating they play a less critical role than Price and Quality. Based on the ANP analysis, Supplier 1 emerges as the preferred supplier, with the highest weight of 0.44, followed by Supplier 2 (0.34) and Supplier 3 (0.22). This study demonstrates that using DEMATEL and ANP enables a more informed, structured supplier selection process, helping ABC Bakery make better procurement decisions aligned with its operational and quality goals.